A novel cryoprecipitate-enriched PRP (Cryo-PRP) gel with enhanced mechanical strength and regenerative capacity accelerates enterocutaneous fistula healing - Zhao, Zhang-Sheng; Wang, Zhen-Zhen; Ye, Hua; Cai, Xian-Lei; Hu, Bin; Han, Qiu; Ma, You-Li (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionEnterocutaneous fistula (ECF) remains a major clinical challenge due to its complex pathophysiology, high recurrence, and limited non-surgical options. Platelet-rich plasma (PRP) has demonstrated regenerative potential, but its limited mechanical strength restricts its application in high‐output fistulas. To overcome this limitation, we developed a cryoprecipitate‐enriched PRP (Cryo‐PRP) with enhanced fibrinogen content and gel stability.MethodsCryo‐PRP was prepared by cryoprecipitation of conventional PRP. Characterization included fibrinogen quantification, thromboelastography (TEG), and scanning electron microscopy (SEM). Therapeutic efficacy was assessed in a rat ECF model by evaluating fistula closure, histological changes, and expression of angiogenic and inflammatory markers.ResultsCryo‐PRP exhibited significantly higher fibrinogen levels (5.26 ± 0.78 g/L vs. 2.58 ± 0.49 g/L, P < 0.001) and greater clot firmness (TEG‐MA: 37.8 ± 2.2 mm vs. 28.7 ± 1.3 mm, P < 0.001) compared with standard PRP. SEM revealed a denser and more organized fibrin network in Cryo‐PRP gels. In vivo, Cryo‐PRP accelerated wound healing, enhanced epithelialization, preserved crypt architecture, and reduced inflammation. Immunostaining demonstrated increased neovascularization (CD34), upregulation of regenerative markers (α‐SMA, CD31, VEGF, PCNA), and suppression of TNF-α expression.DiscussionCryo‐PRP demonstrates superior mechanical and biological properties over conventional PRP, effectively promoting tissue regeneration and reducing inflammation in an ECF model. These findings support Cryo‐PRP as a safe, autologous, and minimally invasive therapeutic strategy for ECF management.